Counter-Stereotypical Career-Related Media Content and Adolescents' Professional Sexism: A Longitudinal Study of Woman Boss Television Series and Social Media Posts. - Vranken, Ilse; Devos, Sarah; Vandenbosch, Laura (Sex Roles, 2023)
Woman boss series and woman boss posts on social media that portray women in stereotypically male professions have attracted scholarly attention. The positive effects of this content on adolescents over time are unclear. This study helped fill this gap by examining the within-person reciprocal relations between exposure to woman boss series and posts and adolescents' beliefs about the male vs. female division of professional tasks according to traditional gender stereotypes (which was labeled as professional sexism). We examined the mediating role of the perceived utility of such content and the moderating roles of hypergender identity and knowing women in counter-stereotypical professions offline. A total of 1,286 late adolescents (M = 18.33, SD = 0.64) participated in a three-wave longitudinal study with a four-month time interval. The findings indicated positive but inconsistent within-person associations between professional sexism and the perceived utility of woman boss series. The results supported the moderating role of knowing women in atypical professions; that is, the perceived utility of woman boss posts on social media in Wave 2 related to professional sexism in Wave 3. The direction of the association changed when considering the extent to which adolescents knew women in atypical professions. Implications for how parents, teachers, and academic school counselors may talk with adolescents about women who are portrayed in atypical occupations in TV series and on social media are discussed.